Adiponectin Enhances B-Cell Proliferation and Differentiation via Activation of Akt1/STAT3 and Exacerbates Collagen-Induced Arthritis - Che, Nan; Sun, Xiaoxuan; Gu, Lei; Wang, Xiaohui; Shi, Jingjing; Sun, Yi; Xu, Lingxiao; Liu, Rui; Wang, Junke; Zhu, Fengyi; Peng, Na; Xiao, Fan; et al. (Frontiers in Immunology, 2021)
Although B cells have been shown to contribute to rheumatoid arthritis (RA) pathogenesis, the precise roles of B cells in RA need to be further explored. Our previous studies have revealed that adiponectin (AD) is highly expressed in the inflamed synovial joint tissue and correlates closely with progressive bone erosion in RA patients. Here, we aimed to investigate a possible role of AD in B cell proliferation and differentiation. We found that AD stimulation could induce B cell proliferation and differentiation in cell culture. Notably, local intraarticular injection of AD promoted B cell expansion in joint tissues and exacerbates arthritic development in collagen-induced arthritis (CIA) mice. Mechanistically, AD induced the activation of PI3K/Akt1 and STAT3 and promoted the proliferation and differentiation of B cells. Moreover, STAT3 bound to Blimp-1 gene promotor, up-regulated Blimp-1 expression at transcriptional level and promoted B cell differentiation. Together, AD exacerbates CIA via enhancing B cell proliferation and differentiation mediated by PI3K/Akt1/STAT3 axis.